Aplikasi Game Edukasi Pengenalan Huruf Hijaiyah Untuk Anak Usia Dini Berbasis Android - Sri Ipnuwati (Jurnal Teknologi dan Informatika (JEDA), 2020)
AbstractFor Muslims, there is an obligation to read, understand, and practice the contents of the Qur'an. But in order to practice and understand the contents of the Koran, you must first be able to read and recognize the hijaiyah letters. To introduce hijaiyah letters to children, it is necessary to use an effective and fun method, which is intended so that children do not experience boredom and stay focused on what is being taught. The case study in the research object was carried out in Babatan village in Katibung District, where the hijaiyah letter recognition method still uses conventional methods, namely using a guidebook called IQRA, besides teaching and learning activities at TPQ are also constrained by rainy weather and holidays that result in learning activities teaching at TPQ will be closed. Based on the description of these problems and increasingly sophisticated technological advances, the researcher proposes to make a game application in the form of educational animation that can make it easier for children in hijaiyah letter recognition patterns, especially ages 3-10 years. The results of this study are the hijaiyah letter recognition educational game application system has been running in accordance with the initial objectives of the study where, the application is able to know and understand the form of letters, distinguish letter forms, how to read letters and sounds of Hijaiyah letters properly and correctly and with the Recognizing Letter Game. The Hijaiyah system is able to attract children's interest in learning at TPQ Al-Muhajirin Babatan Village, Kec. Katibung.